2012
DOI: 10.1371/journal.pone.0035228
|View full text |Cite
|
Sign up to set email alerts
|

Local and Landscape Factors Determining Occurrence of Phyllostomid Bats in Tropical Secondary Forests

Abstract: Neotropical forests are being increasingly replaced by a mosaic of patches of different successional stages, agricultural fields and pasture lands. Consequently, the identification of factors shaping the performance of taxa in anthropogenic landscapes is gaining importance, especially for taxa playing critical roles in ecosystem functioning. As phyllostomid bats provide important ecological services through seed dispersal, pollination and control of animal populations, in this study we assessed the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 111 publications
(197 reference statements)
5
75
0
3
Order By: Relevance
“…In tropical wet forest in Mexico, abundances of the most common bat species were associated positively or negatively with variation in canopy cover across successional stages, rather than with landscape attributes (Castro-Luna et al 2007a). In contrast, a study in Mexican tropical dry forest found evidence for an important role of local (vegetation complexity) and landscape attributes (area and cover of different vegetation types) as determinants of variation in abundance, which were ensemble specific and scale dependent (Avila-Cabadilla et al 2012). In Central Amazonia, gleaning animalivorous phyllostomid bats exhibited greater abundance and richness in Cecropia-dominated regrowth, whereas stenodermatine frugivores were more abundant in abandoned pastures and Vismia-dominated regrowth, demonstrating that different successional trajectories result from differences in land-use history (cutting versus cutting and burning) that lead to distinct differences in bat assemblage composition (Bobrowiec and Gribel 2010).…”
Section: Secondary Forests and Successionmentioning
confidence: 79%
“…In tropical wet forest in Mexico, abundances of the most common bat species were associated positively or negatively with variation in canopy cover across successional stages, rather than with landscape attributes (Castro-Luna et al 2007a). In contrast, a study in Mexican tropical dry forest found evidence for an important role of local (vegetation complexity) and landscape attributes (area and cover of different vegetation types) as determinants of variation in abundance, which were ensemble specific and scale dependent (Avila-Cabadilla et al 2012). In Central Amazonia, gleaning animalivorous phyllostomid bats exhibited greater abundance and richness in Cecropia-dominated regrowth, whereas stenodermatine frugivores were more abundant in abandoned pastures and Vismia-dominated regrowth, demonstrating that different successional trajectories result from differences in land-use history (cutting versus cutting and burning) that lead to distinct differences in bat assemblage composition (Bobrowiec and Gribel 2010).…”
Section: Secondary Forests and Successionmentioning
confidence: 79%
“…Taxonomic identity and time of capture were recorded for each bat. We punchmarked each individual before release with a code in the left wing (Bonaccorso and Smythe, 1972). Punch marks were ephemeral but useful for determining whether a bat had been captured previously.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Bat responses to habitat conversion can be species-, ensembleand habitat-specific (Avila-Cabadilla et al, 2012;Estrada et al, 1993;Fenton et al, 1992;Gorresen and Willig, 2004;Pinto and Keitt, 2008). However, most previous studies examined responses in terms of species abundance and species richness, whereas only a few have considered bat behavioral responses evaluated in terms of temporal activity patterns (Castro-Arellano et al, 2009;Presley et al, 2009aPresley et al, , 2009b.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the nectarivorous Glossophaga soricina occurs at a greater abundance in sites with a high diversity of forest types when considering a 500 m buffer in radius. On the other hand, Leptonycteris yerbabuenae, which is also a nectarivorous species, was influenced by this variable at a scale of 1000 m in a tropical dry forest in Mexico [13]. In contrast, a study carried out in the Amazon showed that bat responses to the landscape varied among species regardless of the analyzed scale [17].…”
Section: Introductionmentioning
confidence: 87%
“…There are much fewer studies on this topic for tropical dry forests in comparison with rainforests especially in Brazil. Nevertheless, a study conducted in a dry forest in Mexico found a negative relationship between the abundance of nectarivorous bats and the size of dry forest fragments and found a positive relationship between the abundance of frugivorous bats and the percentage of riparian forests [13]. Understanding the effects of habitat structure on the bat assemblage is extremely important for interpreting the observed patterns and supporting management plans [14,15].…”
Section: Introductionmentioning
confidence: 99%